The Affordable Care Act: Where are we now?. Issue 5 (May 2018) - Collins, Beth L.; Saylor, Jennifer
Abstract : Delve into this discussion of the Affordable Care Act's impact on nursing, then consider how changes to the law enacted over the past year affect delivery of care to older adults.